Skin to Skin Contact: Newborn Temperature Stability in the Operating Room. Issue 3 (May 2018) - Billner-Garcia, Renee; Spilker, Arlene; Goyal, Deepika
Abstract: Purpose: The purpose of this project was to assess temperature stability in newborns undergoing early intraoperative skin-to-skin contact (SSC) after elective cesarean birth. Method: This feasibility study examined electronic medical record data of 91 mother–baby dyads who participated in early intraoperative SSC after an elective cesarean birth. Infant axillary temperatures were obtained just before initiation and upon completion of intraoperative SSC. Results: The mean age of women in this sample was 35 (SD, 4.2) years. They were an average of 39 4/7 weeks gestation, and largely Caucasian 55% (n = 50) and Asian 30 (33%). Fifty-eight percent (n = 53) of infants were male, weighing an average of 3, 566 g (SD, 401.83). Nineteen (21%) of infants demonstrated no temperature change pre to post SSC, with an increase noted in 32 (35%) infants, and a decrease in 40 (44%). Clinical Implications: Findings provide support for continued intraoperative SSC. Areas for improvement were also identified, for example, missing medical record data. Abstract : Skin-to-skin contact is commonly initiated after vaginal birth of healthy babies, but not for all women giving birth via cesarean to healthy babies. In this study, the feasibility of using skin-to-skin contact in the operating room (OR) for all healthy mothers and babies after cesarean birth was examined using newborn temperature stability as a measure. Results suggest concerns about temperature stability should not be a barrier to implementing skin-to-skin care in the OR after cesarean birth of healthy babies.